Usborne Phonics Readers : Toad Makes A Road - Phil Roxbee Co (London, United Kingdom Usborne Publishing Ltd, 2006)
Combining a phonics-based text with a funny story, the books in this series are aimed at beginner readers. The pictures give clues to the words and fold out flaps on some pages give children the chance to guess what will happen next.
Keywords: PY - Language